Study in vitro and in silico on effectiveness noni fruit extract (Morinda Citrifolia) to reducing hypertension - La Ode Abdul Haris Hijriansyah; Hermilasari Hermilasari; Hardyanty Subair; Irianto Irianto; Andi Alief Utama Armyn; Supartina Hakim (jurnal1, 2020)
Hypertension is one of the major causes of stroke. Stroke can be prevented by controlling hypertension. Noni fruit proved to have antihypertensive effect. Noni Fruit contains scopoletin and xeronin compounds that play a role in antihypertensives. This study aims to determine the effectiveness of noni fruit extract to controlling hypertension. The research method used is pre-test and post-test matched control group. The 6 Wistar rats were divided into 3 groups consisting of 1 treatment group and 2 control groups. Group P1 was induced by using ketamine 0.05 ml + epinephrine 0.2 ml + 6 ml noni fruit extract, group K (-) induced by ketamine 0.05 ml + epinephrine 0.2 ml without extract, and group K (+) induced by using ketamine 0.05 ml + epinephrine 0.2 ml + captopril 2.5 mg. The results showed that epinephrine can be used as a hypertensive inducer. Noni fruit extract as much as 6ml can provide antihypertensive effects. In Vitro, test result showed that noni fruit extract can reduce blood pressure by an average decrease in blood pressure of 58,5 mmHg While captopril 25,5 mmHg. in addition to the in vitro test, the results of the in-silico test showed that the noni fruit extract can significantly reduce blood pressure compared to anti-hypertensive drugs (captopril). the value of scopoletin in noni fruit is -7.6. and captopril only -5.7.